Peran Indonesia sebagai aktor perdamaian dalam penyelesaian konflik Rusia-Ukraina - Saputri, Mahera Yogi (Maliki Interdisciplinary Journal, 2024)
The ongoing Russia-Ukraine conflict since 2014 has had far-reaching implications for global and regional stability. In this situation, Indonesia seeks to take on the role of a mediation and peace actor, utilizing its neutral position and commitment to diplomacy. This study aims to analyze Indonesia's role in mediating and resolving the Russia-Ukraine conflict, as well as identify the supporting and inhibiting factors in its implementation. The results show that Indonesia has adopted a bilateral and multilateral diplomacy approach through direct dialogue with Russia and Ukraine as well as active participation in international forums such as the UN, ASEAN, and G20. Indonesia has also called for a ceasefire and offered to host mediation, in addition to providing humanitarian assistance to conflict victims. At the level of international organizations, Indonesia supports various resolutions at the UN and encourages cooperation in ASEAN to achieve regional consensus that supports peace. The journal also provides information on some of the obstacles Indonesia faces, including limited global influence and domestic political dynamics. Nonetheless, Indonesia's active role in international and regional forums and commitment to the principles of peace show great potential in contributing to the resolution of the Russia-Ukraine conflict. This journal provides important insights into Indonesia's efforts and challenges in resolving the Russia-Ukraine conflict.